Numerical optimization of process parameters in HLLW spray calcination - Feng Gao; Yuzhou Ming; Yajun Zhang; Bochao Wang; Xingyun Jia (PLoS ONE, 2026)
To address the issues of incomplete reactions and potential solids accumulation in high‑level liquid waste (HLLW) spray calcination, this study developed a 3D computational domain utilizing a species transport model to simulate the combustion of a nitric acid, sucrose, and nitrate solution. The impacts of wall heating temperature (200–1200 °C), porous media porosity (0–1), inlet velocity (0.001–0.2 m/s), and reactant concentrations on the sodium oxide (Na 2 O) product mass fraction were systematically investigated. Simulation results demonstrate: (1) wall temperature positively correlates with Na 2 O formation, with the mass fraction rising from 0.089 to 0.360 as temperature increases from 200 °C to 1200 °C; (2) higher porosity facilitates product formation, though growth stagnates within the 0.2–0.8 range; (3) inlet velocity dictates reaction kinetics, peaking at an optimal 0.01 m/s (Na 2 O mass fraction 0.287), whereas velocities >0.05 m/s cause incomplete reactions; and (4) doubling sucrose concentration boosts Na 2 O yield by 115% and 180% more than equivalent increases in nitric acid and nitrates, respectively. Enhancing solid product recovery requires elevating wall temperature, regulating inlet velocity at approximately 0.01 m/s, and optimizing the sucrose reductant ratio.